Uso de la clasificación de Pell y Gregory en el diagnostico radiográfico de terceros molares. - Bonilla Brito, Francheska Tamara (2023)
ABSTRACT: The present research project had a descriptive, qualitative, quantitative, cross-sectional perspective, with the objective of determining the use of the Pell and Gregory classification in the diagnosis of third molars according to digital panoramic radiographs. With a sample of 150 panoramic radiographs that correspond to ages between 17 and 35 years, the radiographs of patients were chosen intentionally in a non-probabilistic way through the selection criteria, therefore, a class I and position A of Pell and Gregory's classification were obtained, predominates in pieces 18 and 28 with a percentage of 29% and 28% respectively, in pieces 38 and 48 it denotes class 1 and position A with a percentage of 34%, in the case of the prevalence of third molar position according to sex, class I and position A prevail in the male sex with 39.20% in tooth 18, the female sex denotes class III and position C with 34.20% in the room 28, class I and position A, the female sex predominates with 36.80% in room 38, while in room 48 there is a higher frequency of females with 36.80% in class I and position A. According to the age group, adulthood was most frequent in tooth 18 with 47.10% in class I and position A; in tooth 28, adulthood was most frequent with 52.90% in class I and position A; in adulthood, class I and position A prevailed with 52.90% in tooth 38; and in tooth 48, adulthood had the highest frequency with 47.10% in class I and position A. In the upper arch it denotes class II and position A with 28% in both pieces 18 and 28, while class I predominates in the lower arch and position A with 34% and the same in teeth 38 and 48. According to the eruption anomalies in pieces 18 and 28 dental impaction predominates in the female sex with 17.10%, in tooth 38 the female sex has pieces with greater dental impaction with a percentage of 31.60 and in piece 48 the percentage of dental impaction is 37.80 % in the female sex. In the same way, surveys were also conducted among students of dentistry at the UNACH to determine the criteria that are used correctly for the diagnosis of third molars.